Comparison of Vs30 Value from Microtremor Data Based on SPT Drill Test of Young Merapi Deposits in Opak River, Yogyakarta - Adelia Saras Nugraheni; Agung Setianto; Hendy Setiawan (Department of Geophysical Engineering, Faculty of Engineering, University of Lampung, 2024)
The 2006 Yogyakarta earthquake was caused by the tectonic movement of the Opak Fault, which is located near the Opak River. This research conducts microtremor data processing and analysis using the Horizontal Vertical Spectral Ratio (HVSR) method and the Inversion method to determine dominant frequency (fo), amplification (Ao), and shear wave velocity to a depth of 30 meters (Vs30) in Opak River area as an effort in earthquake disaster mitigation. The purpose of this research is to compare the Vs30 value of the inversion method using layer parameters according to Standard Penetration Test (SPT) data from previous research and layer parameters according to the number of lithologies. The result presents that the Vs30 values around Opak River are in the range of 183 - 301 m/s and belong to the stiff soil site classification. The comparison shows that the Vs30 values in the two different layer parameters are both still in the stiff soil site classification and have a slight difference in Vs30 values. Thus, the use of microseismic data to determine the Vs30 value is a fast and efficient way to determine the subsurface geology of the study area.